2020
DOI: 10.3126/jkmc.v8i3.29720
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of empathy levels of dental students’ in Nepal: A cross-sectional comparative study

Abstract: Background: Empathy is a behavioural aspect of understanding and communicating with a desire to help. Empathy in medical personnel with patient is one of the basic ingredients of good physician/dentist –patient relationships. Objectives: To assess empathy level among dental undergraduate students, interns and dental postgraduate students of Nepal and to investigate the differences in empathy scores based on gender and year of dental training. Methodology: A cross-sectional questionnaire stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
2
0
5
Order By: Relevance
“…23,38 Other investigators showed either no difference in empathy levels of postgraduates during their clinical training 39,40 or even lower empathy scores in postgraduate students. 18 Several researchers stated that interns had the highest empathy levels in comparison to undergrads, 22,37,[41][42][43] while others showed lower empathy levels in dental interns. 8,17 Changes in dental students 'empathy levels could be associated initially with cultural differences, heritage, faith, passion, affective features, and social behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,38 Other investigators showed either no difference in empathy levels of postgraduates during their clinical training 39,40 or even lower empathy scores in postgraduate students. 18 Several researchers stated that interns had the highest empathy levels in comparison to undergrads, 22,37,[41][42][43] while others showed lower empathy levels in dental interns. 8,17 Changes in dental students 'empathy levels could be associated initially with cultural differences, heritage, faith, passion, affective features, and social behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers stated that interns had the highest empathy levels in comparison to undergrads, 22,37,41–43 while others showed lower empathy levels in dental interns 8,17 . Changes in dental students ‘empathy levels could be associated initially with cultural differences, heritage, faith, passion, affective features, and social behaviors 37,44 .…”
Section: Discussionmentioning
confidence: 99%
“…t değerlendirildiği birçok çalışma bulunmaktadır (2,3,6,7,8,11,12). Amerikan Diş Hekimliği Eğitimi Derneği, sağlıklı diş hekimi-hasta ilişkilerinde empatinin önemli bir rol oynadığını belirterek, empatiyi diş hekimliği eğitimi için en önemli ikinci klinik yeterlilik olarak listelemiş ve empatinin diş hekimliği müfredatına dahil edilmesinin önemini vurgulamıştır (3,8,11).…”
Section: Abstract: Demographic Factors Dental Education Empathyunclassified
“…Bununla birlikte, bir klinisyen için eşit derecede önemli olan diğer bir özellik ise empatidir (5). Empati, iyi bir doktor-hasta ilişkisinin temel "öğelerinden" biridir ve genellikle sağlık çalışanları için önemli bir nitelik olarak kabul edilir (6)(7)(8). Sağlık hizmeti ortamında empati bir hastanın semptomlarından, hastalıklarından etkilenen duygularını nasıl deneyimlediğini anlama yeteneğini ve bu anlayışı hastaya iletme yeteneğini içeren bilişsel ve davranışsal bir nitelik olarak görülebilir (6,8,9).…”
Section: Introductionunclassified
See 1 more Smart Citation